Interdisciplinary Parkinson’s Disease Deep Brain Stimulation Screening and the Relationship to Unintended Hospitalizations and Quality of Life - Higuchi, Masa-aki (PLoS One, 2016)
OBJECTIVE: To investigate the impact of pre-operative deep brain stimulation (DBS) interdisciplinary assessments on post-operative hospitalizations and quality of life (QoL). BACKGROUND: DBS has been utilized successfully in Parkinson’s disease (PD) for the treatment of tremor, rigidity, bradykinesia, off time, and motor fluctuations. Although DBS is becoming a more common management approach there are no standardized criteria for selection of DBS candidates, and sparse data exist to guide the use of interdisciplinary evaluations for DBS screening. We reviewed the outcomes of the use of an interdisciplinary model which utilized seven specialties to pre-operatively evaluate potential DBS candidates. METHODS: The University of Florida (UF) INFORM database was queried for PD patients who had DBS implantations performed at UF between January 2011 and February 2013. Records were reviewed to identify unintended hospitalizations, falls, and infections. Minor and major concerns or reservations from each specialty were previously documented and quantified. Clinical outcomes were assessed through the use of the Parkinson disease quality of life questionnaire (PDQ-39), and the Unified Parkinson’s Disease Rating Score (UPDRS) Part III. RESULTS: A total of 164 cases were evaluated for possible DBS candidacy. There were 133 subjects who were approved for DBS surgery (81%) following interdisciplinary screening. There were 28 cases (21%) who experienced an unintended hospitalization within the first 12 months following the DBS operation. The patients identified during interdisciplinary evaluation with major or minor concerns from any specialty service had more unintended hospitalizations (93%) when compared to those without concerns (7%). When the preoperative “concern” shifted from “major” to “minor” to “no concerns,” the rate of hospitalization decreased from 89% to 33% to 3%. A strong relationship was uncovered between worsened PDQ-39 at 12 months and increased hospitalization. CONCLUSIONS: Unintended hospitalizations and worsened QOL scores correlated with the number and severity of concerns raised by interdisciplinary DBS evaluations. The data suggest that detailed screenings by interdisciplinary teams may be useful for more than just patient selection. These evaluations may help to stratify risk for post-operative hospitalization and QoL outcomes.